Implementation of Discipline and Responsibility Values through Paskibra Extracurricular Activities: - - Nurul Widya Tanjung; Kurniana Bektiningsih (Ainara Journal (Jurnal Penelitian dan PKM Bidang Ilmu Pendidikan), 2026)
Character education is an essential aspect of elementary education aimed at developing students into disciplined and responsible individuals. This study aimed to describe the implementation of discipline and responsibility values through Paskibra extracurricular activities at SD Srondol Wetan 02 Semarang City and to identify the supporting and inhibiting factors affecting its implementation. The research employed a qualitative approach using a descriptive-qualitative method. Data were collected through observation, interviews, and documentation, and analyzed using data reduction, data display, and conclusion drawing techniques. The findings revealed that discipline and responsibility values were instilled through consistent habituation, including punctuality, compliance with trainers’ instructions, responsibility toward tasks and teams, and awareness of individual roles within the group. These values were not only applied during Paskibra activities but were also internalized into students’ daily lives at school and at home. Supporting factors included school support, trainers’ commitment, parental involvement, and structured activity programs, while inhibiting factors involved students’ physical conditions, limited training time, differences in student characteristics, and weather conditions. These findings indicate that Paskibra extracurricular activities contribute positively to strengthening character education among elementary school students.